Medical experience as an influencing parameter in emergency medical care for psychiatric emergencies: retrospective analysis of a multicenter survey - Zujalovic, Benedikt; Mayer, Benjamin; Hensel, Constanze; Schmid, Sebastian; Jungwirth, Bettina; Barth, Eberhard; Muth, Claus-Martin; Katzenschlager, Stephan; Schönfeldt-Lecuona, Carlos (BMC emergency medicine, 2023)
Background: Prehospital care of psychiatric patients often relies on the medical experience of prehospital emergency physicians (PHEPs). The psychiatrists (PSs) involved in the further treatment of psychiatric patients also often rely on their experience. Furthermore, the interaction between PHEPs and PSs is characterized by interaction problems and different approaches in the prehospital care of the psychiatric emergency. Objectives: To analyze the phenomenon of “medical experience” as a cause of possible interaction-related problems and assess its impact on the prehospital decision-making process between prehospital emergency physicians and psychiatrists. Methods: The retrospective data analysis was conducted between November 2022 and March 2023. Medical experience was defined as follows, based on the demographic information collected in the questionnaires: For PHEPs, the period since obtaining the additional qualification in emergency medicine was defined as a surrogate marker of medical experience: (i) inexperienced: < 1 year, (ii) experienced: 1–5 years, (iii) very experienced: > 5 years. For PSs, age in years was used as a surrogate parameter of medical experience: (i) inexperienced: 25–35 years, (ii) experienced: 35–45 years, (iii) very experienced: > 45 years. Results: Inexperienced PSs most frequently expressed anxiety about the psychiatric emergency referred by a PHEP (27.9%). Experienced PHEPs most frequently reported a lack of qualifications in handling the care of psychiatric emergencies (p = 0.002). Very experienced PHEPs were significantly more likely to have a referral refused by the acute psychiatric hospital if an inexperienced PS was on duty (p = 0.01). Experienced PHEPs apply an intravenous hypnotic significantly more often (almost 15%) than PSs of all experience levels (p = 0.001). In addition, very experienced PHEPs sought prehospital phone contact with acute psychiatry significantly more often (p = 0.01). Conclusion: PHEPs should be aware that the PS on duty may be inexperienced and that treating emergency patients may cause him/her anxiety. On the other hand, PHEPs should be receptive to feedback from PS who have identified a qualification deficiency in them. Jointly developed, individualized emergency plans could lead to better prehospital care for psychiatric emergency patients. Further training in the prehospital management of psychiatric disorders is needed to minimize the existing skills gap among PHEPs in the management of psychiatric disorders.
Veröffentlicht: 23. September 2023
Gesehen am 23.11.2023